2017
DOI: 10.1590/s0102-865020170080000003
|View full text |Cite
|
Sign up to set email alerts
|

Inside-out and standard vein grafts associated with platelet-rich plasma (PRP) in sciatic nerve repair. A histomorphometric study

Abstract: Results:In the morphological analysis of all groups, myelinated nerve fibers with evident myelin sheath, neoformation of the epineurium and perineurium, organization of intraneural fascicles and blood vessels were observed. In the morphometry of the distal stump fibers, SVPRP group had the highest means regarding fiber diameter (3.63±0.42 μm), axon diameter (2.37±0.31 μm) and myelin sheath area (11.70±0.84 μm 2 ). IOVPRP group had the highest means regarding axon area (4.39±1.16 μm 2 ) and myelin sheath thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…A meta-analysis of published papers determined that for nerve gaps up to 4 cm in length, vein conduits did not induce any significant improvement in sensory recovery outcome compared to conduits of other materials [170]. However, the axon regeneration-promoting efficacy of vein conduits is enhanced when they are filled with PRP [171][172][173], muscle [174], pre-degenerated muscle [175,176], muscle seeded with neural-transdifferentiated human mesenchymal stem cells [177], and minced peripheral nerves [178]. One study in sheep showed that using the median epineural sheath as a conduit can restore median nerve function across 6-cm-long nerve gaps [179].…”
Section: Conduit Compositionmentioning
confidence: 99%
“…A meta-analysis of published papers determined that for nerve gaps up to 4 cm in length, vein conduits did not induce any significant improvement in sensory recovery outcome compared to conduits of other materials [170]. However, the axon regeneration-promoting efficacy of vein conduits is enhanced when they are filled with PRP [171][172][173], muscle [174], pre-degenerated muscle [175,176], muscle seeded with neural-transdifferentiated human mesenchymal stem cells [177], and minced peripheral nerves [178]. One study in sheep showed that using the median epineural sheath as a conduit can restore median nerve function across 6-cm-long nerve gaps [179].…”
Section: Conduit Compositionmentioning
confidence: 99%
“…A meta-analysis of published papers determined that for nerve gaps up to 4 cm in length, vein conduits did not induce any significant improvement in sensory recovery outcome compared to conduits of other materials [170]. However, the axon regeneration-promoting efficacy of vein conduits is enhanced when they are filled with PRP [171][172][173], muscle [174], pre-degenerated muscle [175,176], muscle seeded with neural-transdifferentiated human mesenchymal stem cells [177], and minced peripheral nerves [178]. One study in sheep showed that using the median epineural sheath as a conduit can restore median nerve function across 6-cm-long nerve gaps [179].…”
Section: Conduit Compositionmentioning
confidence: 99%
“…PRP is an autologous concentrate of platelets in a small volume of plasma containing growth factors released by these cells, which can serve as a matrix for enhancing collagen synthesis, stimulating angiogenesis, accelerating SC migration, and promoting nerve regeneration [13,14]. Once activated by thrombin, PRP filling inside the vein can provide good mechanical support, which does not easily leak out and exerts its effects for a long period [15]. Recent studies also reported that PRP had positive effects on nerve regeneration, in addition to its positive effects on the healing of many types of tissues [16,17].…”
Section: Introductionmentioning
confidence: 99%